Performance Analysis of Mango Fruit Freezing System Using Solar Energy - yudhy kurniawan; Bobi Khoirun; Yusup Nur Rohmat; M. Idrus Al Hamid; Ardiyansyah Yatim (Indonesian Society of Applied Science, 2023)
The use of steam compression refrigeration systems is growing both domestically and commercially. The impact of electrical energy consumption in this sector is quite large compared to the need for electrical energy in other electronic equipment. Various efforts were made to be able to reduce the consumption of electrical energy for the cooling system. One of the efforts made by utilizing the natural potential of energy around is solar energy as a source of electrical energy in the mango freezing unit. This fruit is one of the main commodities in West Java, especially in Indramayu Regency. This study aims to determine the performance of the use of solar energy and the need for electrical energy for freezing mango fruit. In the process, freezing is carried out at temperatures below the freezing point of the ingredients/food. Good freezing usually ranges from -12 oC to -24oC. With this temperature, food can last up to 3 to 12 months. Although for freezing mango fruit, it is necessary to have additional treatment so as not to damage the physical structure and quality of the fruit. The method used is to use solar panels as a source of electrical energy in the mango freezing unit. From the tests carried out with variations in the tilt angle of the solar panels, 0°, 20°, and 40° which then from the calculation analysis it is known the comparative value of performance/efficiency and also the consumption of electrical energy generated from each angle of inclination